Some Womanist Inscriptions in Ebony Reigns’ Song Maame HwÉ›: A Literary Approach - Philomena Ama Okyeso Yeboah; Confidence Gbolo Sanka; Lucy Korkoi Bonku (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Music is a part of life in Ghana. Studying a people’s music brings one closer to understanding them since music and reality are intertwined. Despite this reality, the contribution of popular music to national discourse has not received adequate research attention in Ghana. This paper sets out to study the lyrics of one of the songs of Ebony Reigns (Opoku-Kwarteng Priscilla), a Ghanaian musician who died few years ago. Using the womanist theory, the paper investigates how the tenets of this theory are inscribed in the song, the problems that womanism addresses in the song and their implications to the Ghanaian youth. The researchers conclude from the analysis in the paper that the youth have to use social media with caution; they need to listen to advice from the elderly in choosing life partners and the African woman needs to fight for self-expression and liberation through positive cultural means.